ITO‐Free and Fully Solution‐Processed Semitransparent Organic Solar Cells with High Fill Factors. Issue 8 (5th April 2013) - Guo, Fei; Zhu, Xiangdong; Forberich, Karen; Krantz, Johannes; Stubhan, Tobias; Salinas, Michael; Halik, Marcus; Spallek, Stefanie; Butz, Benjamin; Spiecker, Erdmann; Ameri, Tayebeh; Li, Ning; et al.
Abstract Organic photovoltaic (OPV) solar cells that can be simply processed from solution are in the focus of the academic and industrial community because of their enormous potential to reduce cost. One big challenge in developing a fully solution‐processed OPV technology is the design of a well‐performing electrode system, allowing the replacement of ITO. Several solution‐processed electrode systems were already discussed, but none of them could match the performance of ITO. Here, we report efficient ITO‐free and fully solution‐processed semitransparent inverted organic solar cells based on silver nanowire (AgNW) electrodes. To demonstrate the potential of these AgNW electrodes, they were employed as both the bottom and top electrodes. Record devices achieved fill factors as high as 63.0%, which is comparable to ITO based reference devices. These results provide important progress for fully printed organic solar cells and indicate that ITO‐free, transparent as well as non‐transparent organic solar cells can indeed be fully solution‐processed without losses.